In Vivo 6-([18F]Fluoroacetamido)-1-hexanoicanilide PET Imaging of Altered Histone Deacetylase Activity in Chemotherapy-Induced Neurotoxicity. (20th March 2018) - Fukumitsu, Nobuyoshi; Yeh, Skye Hsin-Hsien; Flores II, Leo Garcia; Mukhopadhyay, Uday; Young, Daniel; Ogawa, Kazuma; Jeong, Hwan-Jeong; Tong, William; Gelovani, Juri G.
Abstract : Background . Histone deacetylases (HDACs) regulate gene expression by changing histone deacetylation status. Neurotoxicity is one of the major side effects of cisplatin, which reacts with deoxyribonucleic acid (DNA) and has excellent antitumor effects. Suberoylanilide hydroxamic acid (SAHA) is an HDAC inhibitor with neuroprotective effects against cisplatin-induced neurotoxicity. Purpose . We investigated how cisplatin with and without SAHA pretreatment affects HDAC expression/activity in the brain by using 6-([ 18 F]fluoroacetamido)-1-hexanoicanilide ([ 18 F]FAHA) as a positron emission tomography (PET) imaging agent for HDAC IIa. Materials and Methods . [ 18 F]FAHA and [ 18 F]fluoro-2-deoxy-2-D-glucose ([ 18 F]FDG) PET studies were done in 24 mice on 2 consecutive days and again 1 week later. The mice were divided into three groups according to drug administration between the first and second imaging sessions (Group A: cisplatin 2 mg/kg, twice; Group B: cisplatin 4 mg/kg, twice; Group C: cisplatin 4 mg/kg, twice, and SAHA 300 mg/kg pretreatment, 4 times). Results . TheK i value of [ 18 F]FAHA was increased and the percentage of injected dose/tissue g (% ID/g) of [ 18 F]FDG was decreased in the brains of animals in Groups A and B. TheK i value of [ 18 F]FAHA and % ID/g of [ 18 F]FDG were not significantly different in Group C. Conclusions . [ 18 F]FAHA PET clearly showed increased HDAC activity suggestive of cisplatin neurotoxicity in vivo, which was blocked by SAHA pretreatment.